Structure of human uropepsin at 2.45 angstrom resolution - Canduri, F.; Teodoro, LGVL; Fadel, V; Lorenzi, CCB; Hial, V; Gomes, RAS; Neto, JR; de Azevedo, W. F. (Munksgaard Int Publ Ltd, 2001)
The molecular structure of human uropepsin, an aspartic proteinase from the urine produced in the form of pepsinogen A in the gastric mucosa, has been determined by molecular replacement using human pepsin as the search model. Crystals belong to space group P2(1)2(1)2(1), with unit-cell parameters a = 50.99, b = 75.56, c = 89.90 Angstrom. Crystallographic refinement led to an R factor of 0.161 at 2.45 Angstrom resolution. The positions of 2437 non-H protein atoms in 326 residues have been determined and the model contains 143 water molecules. The structure is bilobal, consisting of two predominantly beta -sheet lobes which, as observed in other aspartic proteinases, are related by a pseudo-twofold axis. A model of the uropepsin-pepstatin complex has been constructed based on the high-resolution crystal structure of pepsin complexed with pepstatin.